Factors Influencing the Transborder Transmission of Brucellosis in Cattle Between Côte d'Ivoire and Mali: Evidence From Literature and Current Key Stakeholders - Oyetola, Wilfried Délé; Diallo, Kanny; Kreppel, Katharina; Kone, Philippe Soumahoro; Schelling, Esther; Bonfoh, Bassirou; Bada Alambedji, Rianatou (Frontiers in Veterinary Science, 2021)
Brucellosis is one of the main zoonoses affecting ruminants. Cattle and small ruminants are involved in transhumance and trade between Côte d'Ivoire and Mali. The endemic nature of the disease in both countries, connected through transhumance, poses unique challenges and requires more information to facilitate disease surveillance and the development of integrated control strategies. This study aimed to assess the main factors influencing the historical and current transborder transmission of brucellosis between Côte d'Ivoire and Mali. A literature review was conducted and data collection was performed through a participatory, transdisciplinary process by holding focus group discussions and interviews with key stakeholders. Cattle breeders, herdsmen, professionals of animal and human health, border control agents and experts took part. The data was analysed to generate essential new knowledge for transborder brucellosis transmission factors and control strategies. From the literature, the seroprevalence of brucellosis in both countries varied from 11% (1987) to 20% (2013) and 15% (1972-1973) to 5% (2012-2014) in Mali and Côte d’Ivoire respectively. The reduction of seroprevalence in Côte d’Ivoire was the result of the annual vaccination campaigns which lowered it from 28% (1978) to 14% (1984) after an increase due to livestock policy implemented in 1976. The meta-analysis and interviews jointly showed that the cross-border mobility was associated with the livestock development policy in Côte d'Ivoire as well as the ECOWAS act on the free movement of people and goods. This act supported the seasonal transhumance of livestock for access to pasture land in southern humid zones in Côte d’Ivoire. The seasonal mobility for grazing and trade was the main risk factor for the spread of brucellosis between pastoral zones of both countries. The existing legal health framework and border control mechanism do not achieve transborder surveillance to control brucellosis. Existing sanitary regulations should be adapted at regional scale to integrate a joint surveillance of high priority zoonotic diseases like brucellosis at border controls.